The evolution of the China – US relations during Xi Jinping’s presidency - Mingyue, Liu (Journal of the Belarusian State University. International Relations, 2023)
The bilateral relationship between the United States and China is one of the most crucial and complex in the world. In the 21st century, the geopolitical landscape has changed as a result of China’s rise to economic dominance and the United States diminishing role in global production and commerce. There have been numerous ups and downs in the ties between China and the United States ever since Xi Jinping became the President of the People’s Republic of China. The evolution of these ties is reviewed, and the characteristics of each stage are examined.
Keywords: China – US relations; Xi Jinping’s presidency; dispute; cooperation; diplomatic relations; Covid-19; international order; dialogue; technological and cultural exchanges; US Government; protectionism; US President; unilateralism